ANALISIS KESIAPAN GURU DALAM MELAKSANAKAN PEMBELAJARAN KURIKULUM MERDEKA DI SDN. 47 PENANJUNG SEKADAU - Jamjemah Jamjemah; Tomo Djudin; Erlina Erlina; Agung Hartoyo (STKIP Persada Khatulistiwa Sintang, 2022)
This study aims to determine the readiness of teachers at SD Negeri 47 Penanjung in implementing independent curriculum learning. This research is a qualitative research with the type of case study. The subjects were all teachers of SD Negeri 47 Penanjung, Sekadau regency totaling 15 people. The object of this research is a form of readiness in implementing independent curriculum learning. Techniques in data collection in this study using observation and documentation techniques. The results of the data analysis show that the implementation of learning at SD Negeri 47 Penanjung Sekadau is ready to carry out independent curriculum learning. Teacher readiness is categorized as good. Most of the teacher as much as 86.7 % already understand the structure of the independent curriculum. Meanwhile, there are some teachers with a total of 13,3 % who do not understand the structure of the independent curriculum. And most of the teachers as much as 80 % already understand the use of the Platform Merdeka Mengajar. Meanwhile, there are some teachers are some teachers who do not understand the use of the Platform Merdeka Mengajar.